INSTANT NASI TUM INNOVATION WITH VARIATION MATERIAL TO IMPROVE CHEMICAL REACTION LEARNING PROCESS AND STUDENT PRENEURSHIP - Purba Rhisma Sutikno; Sri Jumini; P Parmin; Mila Ariyani; Desty Putri Hanifah; Anisa Triyani (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2024)
Tum rice is a traditional food that is a commodity for the Wadaslintang community. This product can be processed and innovated into fast food. The aim of this research is to understand the concept of chemical reaction rates through the symptoms that occur during the process of making instant tum rice and developing it into a student entrepreneurial product. This research methods used a quantitative, using experiments, pretest and posttest, as well as product assessment methods involving experts. The results obtained are the creation of fast food tum rice, innovation in the form of fast food tum rice which is present to bridge the needs of a fast-paced lifestyle, making people tend to choose instant or fast food without sacrificing aspects of tradition and local wisdom, increasing students' understanding of chemical reaction pathways, as well as improving students' studentpreneur skills which is a strategic step to prepare them to face the challenges of the world of work and business in the future. The impact is that there is a tum rice instant solution that is long-lasting and can be prepared and enjoyed at any time. Instant tum rice is suitable for those who are busy and need fast food but still want to enjoy traditional tastes. Whether at home, the office or when traveling, instant rice tum can be a practical and filling food choice